Geoprocessamento Aplicado a Analise da Vulnerabilidade à Erosão na Bacia Hidrografica do Rio Jaibaras - Ceará - Gomes, Daniel Dantas Moreira (2011)
The river basin Jaibaras located in north-central portion of the state of Ceara, bathing nine municipalities, is an important subbacia the river basin Acaraú. For the analysis of natural resources was considered a watershed as the basic unit for the development of the study, basing himself on the basis of theoretical and methodological in general systems theory and analysis Geosystems were evaluated in their processes of evolution, given the vulnerability erosion. By using remote sensing and GIS has been taken into consideration the territorial dynamics, based on the processes of morphogenesis and pedogenesis. With the analysis of landscape were established five categories of morphodynamic means, and considering the vegetation as a stabilizing factor of the landscape, making possible to determine the degree of vulnerability of each subsystem. The river basin has a diverse landscape Jaiba that directly reflect the conditions governing their use and occupation, these differences were compartmentalized into four environmental systems, Deposits Quarternários Depression Sertaneja, Solid Waste and Plateau sedimentary Ibiapaba, and these systems were subdivided into ten subsystems, each with its natural characteristics that have some degree of homogeneity of countenance, and observing the conditions of use and occupation, setting the main environmental impacts in the basin.